Climate Protection as Ethical Challenge. The Climate Protection Issue in the Encyclical Laudato Si’ - Karaczun, Zbigniew M. (Studia Ecologiae et Bioethicae, 2017)
The halting of anthropogenic climate change is one of the most important challenges faced by the current generation. This issue is one of the topics raised in Pope Francis’ encyclical, Laudato Si’. Based on credible scientific studies showing that man is responsible for the observed changes, the Pope indicates the causes behind the destruction of the climate, points to the scale of its possible consequences, and calls for a more active climate policy. However, Laudato Si’ focuses on the ethical and moral factors, rather than the present technical attempts at mitigating climate change. The aim of this paper is to analyze the ways in which the encyclical calls for climate protection and more active climate policy. It also focuses on analyzing the three main challenges which the Pope formulated in this respect, namely, the need to trust in science, the challenge to solidarity, and a call for a more proactive decision-making process involving more courage and a greater sense of responsibility.